(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Postoperative nausea and vomiting (PONV) is a common complication of anesthesia and surgery. Numerous anti-emetics have been studied to prevent and treat PONV. Methods: This study evaluated the antiemetic efficacy, cost-effectiveness and clinical utility of prophylactic dexamethasone and ondansetron compared with placebo in prevention of postoperative nausea and vomiting after ENT surgery in 90 patients. Results: The incidence of PONV was significantly greater in placebo group than dexamethasone group and ondansetron group (p<0.05). The incidence in the dexamethasone group 10% and ondansetron group 26.66% were comparable p>0.05. The incidence of early (0-6 h) PONV was significantly lower in dexamethasone group and ondansetron group than the placebo group (p <0.05). The early incidence was comparable in the dexamethasone (10%) and ondansetrone (13.33%) group( p>0.05). The incidence of PONV in the late postoperative period (6-24 h) was significantly lower in the dexamethasone group (3.33%) than the ondansetron group (23.33%) P<0.05. Conclusion: Both dexamethasone and ondansetron were more effective than placebo in preventing postoperative nausea and vomiting after ENT surgery but dexamethasone was more effective, less expensive and safer than ondansetron, therefore, it may be better substitute for ondansetron. Bangladesh J Otorhinolaryngol; April 2018; 24(1): 14-21